Unitary and non-unitary N = 2 minimal models - Creutzig, Thomas; Liu, Tianshu; Ridout, David; Wood, Simon (Journal of High Energy Physics, 2019)
The unitary N = 2 superconformal minimal models have a long history in string theory and mathematical physics, while their non-unitary (and logarithmic) cousins have recently attracted interest from mathematicians. Here, we give an efficient and uniform analysis of all these models as an application of a type of Schur-Weyl duality, as it pertains to the well-known Kazama-Suzuki coset construction. The results include straight-forward classifications of the irreducible modules, branching rules, (super)characters and (Grothendieck) fusion rules.
CRIS-Team Scopus Importer:2024-06-24
Keywords: Conformal and W Symmetry; Conformal Field Theory; Sigma Models